2021
DOI: 10.4103/jfmpc.jfmpc_2440_20
|View full text |Cite
|
Sign up to set email alerts
|

Total knee replacement at Southwestern Saudi Arabia

Abstract: Background: Knee replacement enables the surgical management of end-stage knee joint osteoarthritis. In Saudi Arabia, there has been a recent increase in total joint replacement surgery. However, there is insufficient literature regarding patient outcomes in this region. Here, we assessed characteristics of patients who underwent total knee arthroplasty and their improvements on knee society score, timed up and go test, and 2-min. walk test. Methods: Patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The first TKA was performed in 1986. The advancement in surgical techniques has enhanced its efficacy [ 6 ]. The National Joint Registry declared that more than 100,000 knees are replaced in the United Kingdom yearly [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first TKA was performed in 1986. The advancement in surgical techniques has enhanced its efficacy [ 6 ]. The National Joint Registry declared that more than 100,000 knees are replaced in the United Kingdom yearly [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“… 3 Few studies from Saudi Arabia have reported the outcomes and quality of life after total knee replacement. 4 However, there is a paucity of data regarding the outcomes of simBTKA in Saudi Arabia in the literature. Therefore, this study aimed to delineate the characteristics of patients who underwent simBTKA and the outcomes of surgery.…”
mentioning
confidence: 99%